Proteomics of acquired enamel pellicle in volunteers with gastroesophageal reflux with dental erosion or not - Martini, Tatiana (2017)
This study compared the protein profile of the acquired enamel pellicle (PAE) in 1) volunteers with gastroesophageal reflux disease (GERD) and dental erosion (BEWE 9 or grade 3 in the upper anterior sextant, all incisors affected; GE group); 2) volunteers with GERD without dental erosion (BEWE=0; GNE group) and 3) control volunteers (without GERD and dental erosion; BEWE = 0; C group). Twenty four subjects (8 in each group) participated. After dental prophylaxis, the AEP was allowed to form during 120 min and was then collected from the vestibular surface of the upper and lower teeth, with filter paper pre-soaked in 3% citric acid. After protein extraction, the samples were submitted to reverse phase liquid chromatography coupled to mass spectrometry (nLC-ESI-MS/MS). Label-free proteomic quantification was performed using Protein Lynx Global Service (PLGS) software. In total, 458 proteins were identified. Seventy-six proteins were common to all the groups. The proteomic profile of the AEP was quite different among the distinct groups. The numbers of proteins exclusively found in the C, GE and GNE groups were 113, 110 and 81, respectively. Most of the proteins exclusively identified in the C and GNE groups bind metals, while those in the GE group are mainly membrane proteins. Many proteins were found exclusively in the reflux groups. Heat-shock proteins were not found in GE. Histatins and Histones were not found in GNE, while Serine/threonine-protein kinases were only identified in GNE. In the quantitative analysis, when the GNE group was compared with the GE group, the proteins with the highest decreases were Lysozyme C, Antileukoproteinase, Cathepsin G, Neutrophil defensins and Basic salivary proline-rich proteins, while those with the highest increases were subunits of Hemoglobin, Albumin and isoforms of Cystatin. Profound alterations in the proteomic profile of the AEP were seen in GNE compared with GE volunteers, which might play a role in the resistance to dental erosion seen in the first.